Aid effectiveness: Human rights as a conditionality measure. (October 2022) - Douch, Mustapha; Edwards, Huw; Landman, Todd; Mallick, Sushanta
Highlights: The 'Aid conditionality' hypothesis proposes effective aid allocation conditional upon recipient country's domestic policies. We focus on human rights as a non-economic dimension of development reflecting repression and corruption in a country. Using LDCs data, we find the growth effect of aid receipts to be consistently positive in countries with better human rights. Sound human rights can be seen as underpinning stronger institutions in lowering repression and corruption. Monitoring human rights provision should act as a tool to help gauge the effectiveness of foreign aid. Abstract: The 'aid conditionality' hypothesis as documented in the literature suggests that aid is effective in augmenting growth only in the presence of a sound policy environment. This hypothesis was so influential that its policy recommendation, to provide aid conditional upon recipient domestic policies, is currently the dominant ODA allocation criterion. However non-economic dimensions of development (political and institutional) are increasingly seen as fundamental. For this reason, this paper focuses on the linkage between aid and a non-economic factor like Human Rights (reflecting repression and corruption) as a measure of aid effectiveness, in explaining growth outcomes across 42 Least Developed economies. We find that countries with better protection of human rights experience positive growth from aid receipts, signifying the role of stronger institutions in enabling more effective use of aid. The paper thus concludes that the measurement and monitoring of human rights provision is a useful tool in gauging the likely effectiveness of foreign aid.